2020
DOI: 10.1039/c9ta09920d
|View full text |Cite
|
Sign up to set email alerts
|

Support effect boosting the electrocatalytic N2 reduction activity of Ni2P/N,P-codoped carbon nanosheet hybrids

Abstract: A Ni2P/N,P-codoped carbon nanosheet were prepared. The N,P-C substrate is regarded as an electronic storage medium which playing a vital role in inhibiting the adsorption of H+ and promoting activation of N2 molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…As observed in Figure a, N 2 ‐TPD spectrum of NiTe‐800 exhibit stronger binding strength and larger desorption peak than that of NiTe‐700, suggesting the rich nitrogen‐adsorption actives sites of exposed {001} facets. [ 11 ] NiTe‐800 also possess higher electrochemical active surface area value of 36.1 mF cm −2 in comparison with that of NiTe‐700 (33.2 mF cm −2 ), which demonstrates that {001} facets are favorable for exposing more active sites (Figure 5b; Figure S9, Supporting Information). Furthermore, the charge transfer resistance ( R ct ) under NRR‐operating condition was further explored by electrochemical impedance spectroscopy (EIS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As observed in Figure a, N 2 ‐TPD spectrum of NiTe‐800 exhibit stronger binding strength and larger desorption peak than that of NiTe‐700, suggesting the rich nitrogen‐adsorption actives sites of exposed {001} facets. [ 11 ] NiTe‐800 also possess higher electrochemical active surface area value of 36.1 mF cm −2 in comparison with that of NiTe‐700 (33.2 mF cm −2 ), which demonstrates that {001} facets are favorable for exposing more active sites (Figure 5b; Figure S9, Supporting Information). Furthermore, the charge transfer resistance ( R ct ) under NRR‐operating condition was further explored by electrochemical impedance spectroscopy (EIS).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Ni is one of the most desirable active site since it can directly catalyze N 2 into NH 3 , while the weak adsorption of hydrogen at Ni sites lead to extremely sluggish catalytic kinetics of the competitive HER. [ 11 ] It is found that Ni‐based species are capable of promoting NRR by transferring the d‐orbital electron to the NN anti‐bonding orbital. [ 12 ] Various strategies are proposed to enhance NRR performance of Ni‐based electrocatalysts including doping engineering, [ 12 ] composition regulation, [ 13 ] coordination state adjustment, [ 8 ] substrate incorporation, [ 14 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…−1 with a FE of 17.21%, 22.89%, and 19.82% was attained in 0.1 m HCl, 0.2 m PBS, and 0.1 m KOH, respectively, where the electronic distribution on catalysts was optimized due to the incorporated dopant. [ 97 ] A novel hierarchical hollow nanotube of NiFeV‐layered double hydroxide on CoVP heterostructures was also reported toward high‐efficient e‐NRR under an universal‐pH condition. [ 93 ]…”
Section: Electrocatalystsmentioning
confidence: 99%
“…The Haber-Bosch process is typically carried out at high temperatures (400-500 °C) and pressures (200-300 atm) where nitrogen from the atmosphere reacts with hydrogen produced from non-renewable resources to produce NH 3 [9][10][11] and consumes ~1-2% of global energy [12][13][14][15][16][17] . Electrochemical nitrogen reduction reaction (ENRR) to produce NH 3 at a small scale near the agricultural fields at ambient conditions using the electricity generated from renewable resources (e. g. solar and wind energy) is a promising alternative to carbon/energy intensive Haber-Bosch process [18][19][20][21][22][23][24][25][26] . N 2 is a stable molecule and its activation and transformation at ambient conditions are challenging 27,28 .…”
Section: Introductionmentioning
confidence: 99%